The ecological crisis in the structure of contemporary global problems - Goncharenko, Marina (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2014)
Researching the threat of global ecological catastrophe the author asserts that not only the natural environment but also the whole contemporary civilization is on the threshold of unpredictable changes. The acuteness of crisis phenomena in the modern world is caused not only by ecological or socio-economic constituent but also by their synergetic impact. The continuing globalization of ecological crisis both in horizontal (geographical) and in vertical (differently directed interaction of human activity, nature and society) dimensions produces also the appearance of anthropological crisis. One of the most important tasks in overcoming the negative trends of crisis phenomena in the development of socio-natural system in the author’s opinion is the adoption of anti-entropic mechanisms for this system preservation, or in other words the implementation of fundamental transformation of spiritual and cultural potential of civilization